2009
DOI: 10.1016/j.ypmed.2009.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted school-based intervention to reduce risk for type 2 diabetes in at-risk youth

Abstract: Objective-To evaluate the impact of a multifaceted, school-based intervention on inner city youth at high risk for type 2 diabetes mellitus (T2DM) and to determine whether the addition of coping skills training (CST) and health coaching improves outcomes.Method-198 students in New Haven, CT at risk for T2DM (BMI > 85 th percentile and family history of diabetes) were randomized by school to an educational intervention with or without the addition of CST and health coaching. Students were enrolled from 2004-200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 35 publications
(34 reference statements)
3
40
0
2
Order By: Relevance
“…These results are partially shared in the literature [18,[27][28][29][30]. One school-based program among Mexican-American youth at risk for T2DM, similar to this study, shows the importance of creating a comprehensive network of activities in the classroom, the home, and the school environment, with these schools having youth with improved physical fitness and reduced body fat [31].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results are partially shared in the literature [18,[27][28][29][30]. One school-based program among Mexican-American youth at risk for T2DM, similar to this study, shows the importance of creating a comprehensive network of activities in the classroom, the home, and the school environment, with these schools having youth with improved physical fitness and reduced body fat [31].…”
Section: Discussionsupporting
confidence: 80%
“…One school-based program among Mexican-American youth at risk for T2DM, similar to this study, shows the importance of creating a comprehensive network of activities in the classroom, the home, and the school environment, with these schools having youth with improved physical fitness and reduced body fat [31]. Another study among Latino and African youth at risk for T2DM utilized a schoolbased program that included nutrition and physical activity education and coping skills training found decreases in BMI, plasma glucose and depression [30]. Additional school-based intervention studies with youth in grades 2-4 showed similar post-intervention results of youth in the intervention group, with statistically significant relative decreases in BMI [18,27]; however, the studies showed no changes in PE class attendance [18,28].…”
Section: Discussionsupporting
confidence: 67%
“…46 Although there have been few large-scale studies of type 2 diabetes prevention or management in youths with the exception of the TODAY study, 47 our group recently conducted a smaller efficacy trial of a multifaceted, school-based intervention (nutrition and physical activity education and coping skills training) aimed at prevention of type 2 diabetes in a high-risk, minority population (n = 198, 55% African-American, 42% Hispanic) of adolescents at risk for type 2 diabetes by virtue of obesity and family history of diabetes. 48 In this study, schools were randomized to two intervention groups to avoid individual contamination: educational intervention with or without the addition of coping skills training and health coaching. Students were followed for 12 months.…”
Section: Evidence For Coping Skills Training With Children and Adolesmentioning
confidence: 99%
“…The HEALTHY Study Group (12) , aplicó en 42 escuelas, una estrategia multidisciplinaria que incluía los componentes de nutrición, conocimientos y habilidades, comunicación y marketing social; obteniendo reducciones significativas de indicadores metabólicos como obesidad/sobrepeso (p=0,03) o glicemia e insulina sérica (p=0,04). Asimismo, Grey et al (11) , implementaron también un programa educativo integral, que agregaba clases de estrategias de afrontamiento de problemas y consejería telefónica a la intervención educativa habitual, para la prevención de la diabetes mellitus tipo 2 en 198 estudiantes con una edad promedio de 12 años, y factores de riesgo como obesidad o sobrepeso.…”
Section: Discussionunclassified
“…Al ser la obesidad y sobrepeso, los factores de riesgo modificables más importantes para la aparición de DM2 en niños, es importante desarrollar programas educativos que incidan en el control del peso corporal y la adopción de estilos de vida saludables (10) . Experiencias anteriores en otros países han tenido efectos contradictorios, probablemente debido al uso incorrecto de los componentes encargados de la modificación sostenible de conductas de riesgo (11,12) . Uno de estos componentes es la educación para la salud, la cual aborda, además de la transmisión de la información, el fomento de la motivación, las habilidades personales y la autoestima, necesarias para adoptar medidas destinadas a mejorar la salud (13) .…”
Section: Introductionunclassified